Calidad de atención al cliente en el Agroquimico Agrozam de la Parroquia La Unión - Cumbicos Bajaña, Alexis Alexandra (2021)
The quality of customer service is one of the main purposes to be achieved by organizations and represents the main reason for transformation for the establishment of a management model that allows the development of strategic actions aimed at the search for satisfaction customer or user, the importance of proper care encourages higher levels of customer loyalty. The research carried out at the agrochemical Agrozam aims to analyze the quality of customer service and the relationship between problematic situations identified in business management, such as the weak empowerment of the chemical products offered, inappropriate organizational behavior and a weak process of personalized assistance to the people who require the products or supplies offered by the institution. The case study is made up of the following methodology: descriptive and documentary types of research, because it allows the ordering of the information obtained for the identification of the main investigative findings, in addition, the inductive and synthetic methods were used, which made possible the detailed analysis of the main problem and the consequences generated in the commercial process, while the technique used is the survey aimed at the consumer market of the company, obtaining as main conclusions that human talent does not have appropriate levels of knowledge about chemical products and that the administration of the agrochemical Agrozam develops empirical practices in its administrative and commercial activities where there is no adequate inventory control to facilitate adequate attention.